Volunteer activity as a means of self-realization and personal selfdetermination - Iryna Didukh (Vasyl Stefanyk Precarpathian National University, 2018)
The article presents the tendency of regeneration and active development of such social phenomenon as volunteering in the life of a modern Ukrainian society. Volunteering nowadays has an important place in the formation of the spiritual culture, values and basic standards of the morality of a person and the society in general. Key words: volunteering, volunteer, charity, virtuousness, motive, reason.